Making Colombia's Tax Policy More Efficient, Fair and Green - Daude, Christian (OECD Economics Department Working Papers, 2015)
Tax revenues at 20% of GDP remain low compared to other Latin American countries and the OECD average and tax evasion is pervasive. Lower oil revenues and the expiration of a number of taxes are putting strains on the budget at a time when social and development spending needs are rising. Heavy reliance on corporate income taxes reduces investment. At the same time, the redistributive impact of taxation is reduced because most of income and wealth taxes are paid by firms rather than households. Therefore, Colombia needs a comprehensive tax reform that boosts revenues and shifts the tax burden to support more inclusive and green growth. Tax loopholes and exemptions that reduce the tax base and favour mainly the rich should be reduced significantly. Strengthening the tax administration will help reduce evasion. This Working Paper relates to the 2014 OECD Economic Survey of Colombia. (www.oecd.org/eco/surveys/economic-survey-colombia.htm)